Prostatic Metastasis Mimicking a Ligamentum Flavum Cyst in Thoracic Spine: A Case Report - Choong, Chee Leong; Lee, Chee Kean; Thamasegaran, Kularaja; Choy, Ker Woon (Malaysian Journal of Medicine and Health Sciences, 2023)
A rare finding of a prostatic carcinoma metastasized in a ligamentum flavum at thoracic spine causing posterior column spinal cord compression. We reported a man with prostatic carcinoma presented with ataxic gait. Magnetic resonance imaging revealed an extradural cystic mass adjacent to the T4 intralaminar region indenting on the spinal cord. T4 posterior decompression via en bloc excision of the ligamentum flavum cyst and laminectomy was performed. Histopathology confirmed glandular tissue within the cyst wall which corresponds to prostatic adenocarcinoma cells. Two months post-operative, patient showed improvement in his muscle strength on left L2 myotome. The preoperative diagnosis is a challenge because of the ligamentum flavum cysts rarity in the thoracic spine and non-specific clinical signs and symptoms. To our best knowledge, this is the first report of metastatic adenocarcinoma of the prostate found as ligamentum flavum cysts.